Corporate Responsibility under the ECSI model: An application in the hotel sector - María-Ángeles Revilla-Camacho; Francisco-José Cossío-Silva; Beatriz Palacios-Florencio (European Research on Management and Business Economics (ERMBE), 2017)
This article deals with the study of Corporate Responsibility (CR) under the European Customer Satisfaction Index (ECSI). The methodology of this empirical study, conducted among 629 customers staying at hotels in the city of Seville, is based on structural equation modeling (PLS). The results obtained demonstrate the applicability of the European model to the hotel sector, although not all the relationships from the original model have been proven. The main contributions are derived from a better understanding of the model's components, a variable not studied before having been incorporated: the importance of Corporate Responsibility (CR). Moreover, it means to contribute to the field of research on CR as, despite the growing interest in the subject, the effects of this construct are still poorly understood.
Keywords: M14; M31; 650; Corporate Responsibility; ECSI; Hotel sector; Structural equation modeling